Diabetic Macular Ischemia Diagnosis: Comparison between Optical Coherence Tomography Angiography & Fundus Fluorescein Angiography - Hossam El-din Mohamed Ahmed Khalil; Mohamed Osman Abd-El Khalek; Ahmed Abd Elsattar Elnoby (Egyptian Journal of Medical Research, 2021)
Background: OCT-A is developing as a new non-invasive rapid technique which may replace FFA as a gold standard procedure for diagnosis of DMI.  Aim of the Work: Comparison between fluorescein angiography (FA) and optical coherence tomography angiography (OCTA) for imaging of foveal avascular zone (FAZ) in diabetic retinopathy patients (DR) affected and not affected by diabetic macular ischemia, (DMI). Subjects and Methods: In this prospective study, 30 eyes for 30 patients and separated by macular status as 19 eyes with DMI and 11 eyes without DMI instructed to undergo OCT-A scan, FFA. Full ophthalmological examination was done and patients signed their informed consents. Results: Of the 30 patients, 13 females and 17 males with a mean age of 52.63 ± 11.9 years. 17 eyes with DMI and 13 eyes without DMI have underwent full ophthalmological examination, BCVA measurement, FFA and OCT-A. BCVA was higher among eyes without DMI (0.5 ±0.2) as compared with eyes with DMI (0.25 ±0.2). Mean time for FFA was 9.4 ± 3.2 m and for OCT-A was 1.5 ± 0.8 m. OCTA can save time than FFA by 85%. 57% was affected with artifacts with OCT-A while 7% has allergic reactions to flourescien dye. Subjects with DMI presented a mean area on FA and OCTA of 0.85 ± 0.2 mm2 and 0.79± 0.2 mm2, respectively (p < /em> = 0.001). Patients without DMI presented a mean area on FA and OCTA of 0.39 ± 0.1 mm2 and 0.36 ± 0.1 mm2, respectively (p < /em> = 0.01). The ICC for the FAZ measurements between the 2 observers on FA and OCTA was 0.98 and 0.99, respectively. Conclusion: OCTA represents a novel technique to diagnose DMI and it may become an alternative to FA for this purpose.